Hazard assessment and formation mechanism of debris flow outbursts in a small watershed of the Linxia Basin - Yang, Weimin; Wan, Feipeng; Ma, Siqi; Qu, Jingkai; Zhang, Chunshan; Tang, Haibing (Frontiers in Earth Science, 2023)
The Linxia Basin is located in the transition zone between the Qinghai-Tibet Plateau and the Loess Plateau in China. Collapse-landslide-debris flow geological disasters have developed in this region. Taking a debris flow that occurred in the western gully of Zhangjiayuan, Dongxiang County as an example, the formation mechanism is studied through field investigation and remote sensing interpretation methods. The hazard and influence range of the debris flow are analysed under different precipitation conditions using numerical simulations. The results show that the western gully experiences medium- to small-scale, rapid and catastrophic viscous mud flows with activity frequencies ranging from medium to high. Because large numbers of landslides, collapses and overland flows develop on the gully bank slope, material sources for debris flows are rich but are supplied intermittently. Induced by heavy rainfall, the landslide disaster mass on the bank slope blocked the gully and formed a weir dam. With water converging in the gully, the dam body was softened to mud, seepage deformation occurred, and the dam then bursts to form a debris flow. This disaster mode represents a kind of rainfall-type landslide-blockage-debris flow disaster chain. Under the varying conditions in which heavy rainfall occurs once every 10 years or once every 50 years, debris flows break out in the western gully, and the Zheda highway and the associated tunnels located below the gully are located in medium-high debris flow danger zones. When a debris flow rushes out of the gully mouth and cannot be discharged in time, it will accumulate and bury these roads and tunnels. Therefore, attention should be given to preventing such small-scale sudden debris flow disasters and to strengthening the early warning capacity of debris flow prevention to ensure the safe operation of highways.